Characterization of a Novel Cross-Linked Lipase: Impact of Cross-Linking on Solubility and Release from Drug Product - Hetrick, Evan M; Sperry, David C; Nguyen, Hung K; Strege, Mark A (Molecular pharmaceutics, 2014)
Liprotamase is a novel non-porcine pancreatic enzyme replacement therapy containing purified biotechnology-derived lipase, protease, and amylase together with excipients in a capsule formulation. To preserve the structural integrity and biological activity of lipase (the primary drug substance) through exposure of the drug product to the low-pH gastric environment, the enzyme was processed through the use of cross-linked enzyme crystal (CLEC) technology, making the lipase-CLEC drug substance insoluble under acidic conditions but fully soluble at neutral pH and in alkaline environments. In this report we characterize the degree of cross-linking for lipase-CLEC and demonstrate its impact on lipase-CLEC solubility and release from the drug product under relevant physiological pH conditions. Cross-linked lipase-CLEC was characterized via size exclusion chromatography (SEC) and capillary electrophoresis sodium dodecyl sulfate polyacrylamide gel electrophoresis (CE-SDS–PAGE). A combination of methodologies was developed to understand the impact of cross-linking on drug product release. Dissolution evaluation using USP Apparatus 2 at pH 5.0 with an enzyme activity-based end point demonstrated solubility discrimination based on degree of cross-linking, while full release was demonstrated at pH 6.5. The dissolution of the drug product was also evaluated using a dual-stage test employing a USP Apparatus 4 flow-through system to mimic the changing pH environments experienced in the stomach and intestine to understand the impact of cross-linking on drug product performance. Use of USP Apparatus 4 to characterize the pH-dependent release of lipase-CLEC represents a novel approach compared to the Apparatus 1 test employing an acid-challenge stage outlined in the USP for delayed-release pancrelipase, and the advantages of this approach may prove useful for understanding the pH-dependence of release for other drug products. Collectively, these studies confirmed that degree of cross-linking is a critical parameter that may impact in vivo release of lipase-CLEC, and also provided a risk assessment tool for understanding the potential impact of under- and over-cross-linked drug substance.